2017
DOI: 10.3892/mmr.2017.6481
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and differentiation of direct co-culture of bone marrow mesenchymal stem cells and pigmented cells from the ciliary margin

Abstract: Damage of retinal ganglion cells (RGCs) is the major consequence of glaucoma and regeneration of RGCs is extremely difficult once the damage has occurred. Retinal stem cells (RSCs) are considered an ideal choice for RGC regeneration. Pigmented cells from the ciliary margin (PCMs) have great retinal differentiation potential and may be an ideal RSC candidate. However, the ciliary margin is too small, so the number of cells that can be obtained is limited. Bone marrow-derived mesenchymal stem cells (BMMSCs) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Results obtained following MSC-based treatments are summarized in Table 2 . Most of them indicate an improved RGC survival, a production of functional RGC-like cells, and an expansion and differentiation of resident retinal stem cells in mature RGCs[ 42 , 43 ]. Although intravitreal administration often produces an exiguous number of MSC engraftments and retinal differentiation, beneficial effects are also attributable to MSC release of neurotrophic factors[ 36 ].…”
Section: Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…Results obtained following MSC-based treatments are summarized in Table 2 . Most of them indicate an improved RGC survival, a production of functional RGC-like cells, and an expansion and differentiation of resident retinal stem cells in mature RGCs[ 42 , 43 ]. Although intravitreal administration often produces an exiguous number of MSC engraftments and retinal differentiation, beneficial effects are also attributable to MSC release of neurotrophic factors[ 36 ].…”
Section: Glaucomamentioning
confidence: 99%
“…Although intravitreal administration often produces an exiguous number of MSC engraftments and retinal differentiation, beneficial effects are also attributable to MSC release of neurotrophic factors[ 36 ]. Co-culturing BMSCs with pigmented cells from the ciliary margin, the photoreceptor specific marker, cone-rod homeobox (Crx), was found increased at both mRNA and protein expression levels[ 43 ]. In addition, MSC retinal differentiation was supported by increased percentages of cells that were immunopositive for typical retinal markers such as rhodopsin, visual system homeobox 2 and heparin sulphate.…”
Section: Glaucomamentioning
confidence: 99%
“… 8 MSCs can also repopulate RGCs through generating RGC-like cells and through facilitating proliferation and differentiation of residential retinal stem cells. 9 , 10 Rui Liu et al . showed that vitreous injection of human umbilical cord MSCs have provided a protection for RGCs in an acute ocular hypertension mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs produce neurotrophins which promote survival and regeneration of injured RGCs in glaucomatous eyes [6]. MSCs are able to repopulate RGCs by generating functional RGC-like cells and by promoting expansion and differentiation of residential retinal stem cells (RSCs) in mature RGCs [7,8]. Additionally, MSCs may modulate function of TM cells and maintain TM integrity enabling alleviation of IOP in glaucomatous eyes [9].…”
Section: Introductionmentioning
confidence: 99%
“…Since the ciliary margin area is very small and proliferation ability of PCMs is limited, only a small number of patients' own PCMs may be isolated and used for autologous transplantation [78,80]. Recently, Li and colleagues revealed that coculture of PCMs with BM-MSCs significantly increased the proliferation rate of PCMs and notably enhanced their differentiation in functional RGCs [8]. Major markers of retinal differentiation, including rhodopsin, visual system homeobox 2, heparin sulfate, and photoreceptor-specific homeobox gene (cone-rod homeobox, Crx), were remarkably upregulated in PCMs following coculture with BM-MSCs, indicating that BM-MSC-based priming of PCMs should be further explored as a new approach which could enable autologous transplantation of RGCs in glaucoma patients [8].…”
mentioning
confidence: 99%